An unusual case of atrophic mandible fracture in a patient with osteogenesis imperfecta and on oral bisphosphonate therapy: Case report - Abdulrahman Al-Osaimi; Mahmood Samman; Mohammad Al-Shakhs; Faisal Al-Suhaim; Sundar Ramalingam (Elsevier, 2014)
Fractures of severely atrophic (height < 10 mm) edentulous mandibles are infrequent and challenging to manage. Factors such as sclerotic bone and decreased vascularity combined with systemic diseases complicate the management of such fractures. Osteogenesis imperfecta (OI) is a heterogeneous group of inherited disorders of type I collagen metabolism. Patients with OI characteristically present with histories of long bone fractures, deformities, blue sclerae, and opalescent dentin. However, fractures of the facial skeleton are rare. Bisphosphonate therapy has been proven to effectively reduce the fracture risk in patients with OI. The purpose of this clinical report is to present an unusual case of spontaneous fracture of the atrophic mandible in a patient with OI. Despite open reduction and internal fixation (ORIF) with miniplate osteosynthesis, the patient developed a second fracture at a screw placement site distal to the first fracture. The patient was successfully treated with ORIF using locking reconstruction plates fixed in the symphyseal and angle regions. Bone healing following ORIF was normal, and no clinical sign of osteonecrosis as a result of bisphosphonate therapy was observed. Patients with OI can present with spontaneous fractures of already weakened mandibles. Although such fractures can be managed with care using established protocols, further research is required to examine the effects of concomitant medication, such as bisphosphonates. Keywords: Atrophic mandible, Mandible fracture, Osteogenesis imperfecta, Bisphosphonates